Enter Beauty of Conservation photo contest (Southeast Farm Press, 2020)
“The beauty of conservation is certainly in the eye of the beholder, and we are eager to see what people across Iowa and beyond see when they think about soil and water conservation, and conservation practices being used on farms,” says Jacqueline Comito, ILF director. Suggested subjects include in-field practices, edge-of-field practices, farming with conservation practices, and livestock, people and pets. 4. Extend ILF outreach This contest is one program ILF is launching to augment its outreach efforts during restricted face-to-face engagements related to the COVID-19 pandemic.